Faculty readiness for a digital education model: A self-assessment from health sciences educators - Olivares Olivares , Silvia Lizett; Lopez, Mildred; Martinez , Roman; Nigenda Alvarez , Juan Pablo; Valdez-García, Jorge E. (Australasian Journal of Educational Technology, 2021)
During the COVID-19 pandemic, the continuity of education across the world is being supported through e-learning. Healthcare programs especially, require continuing patient-centered training to benefit individuals and society. The objective of this study was to assess the faculty members’ skills to continue educational services through a digital education model at the beginning of the lockdown. The methodology consisted in a quantitative approach descriptive and cross-sectional design. The instrument was a survey with two sections: (1) self-assessment and (2) self-ranking based on the digital education model. The results for 497 participants indicated higher scores on active learning and web conference digital skills. Evaluation is still a competence required to be reinforced by the faculty to incorporate a full transition into online learning. There seems to be an agreement about faculty readiness to implement different active learning strategies, despite being in a distance education model. Implications for practice: University leaders welcomed the self-assessment that faculty members performed on digital skills as it allowed them to adapt the training programs and designate staff teams to support the educators once classes restarted. Educators implementing a digital education model should consider a planned and structured educational solution that is beyond the distance between learners and teachers, but an engaging environment for learning incorporating different technologies and active pedagogies.